THE EFFECT OF CHANGING PRICE LEVELS UPON THE DETERMINATION, REPORTING, AND INTERPRETATION OF INCOME. - Graham, Willard J. (The Accounting Review, 1949)
Income, as ordinarily computed and reported, arises primarily from two related but to some extent independent sources. There is the margin between selling price and current cost of acquisition and setting-the cost at the time of the sale. There is the so called "gain" or "loss" arising from the change in price between the time of acquisition and the time of sale, or between acquisition and consumption. This has been called "price profit," or "price loss," or "market profit" or "market loss." The effect of changing price levels upon periodic income has created a problem that accountants should solve now. If it is at all possible, action should be taken before the issuance of the 1948 annual corporate reports. The problem is so important that its solution cannot be deferred until a stable price level would make it practicable for business as a whole to make the change at the same time. Most of the methods used to determine cost of goods sold on a current cost basis do not yield accurate results because not all of the elements of cost are so computed.